Avoiding or accepting conflict in public talk - Duchesne, Sophie; Haegel, Florence (British Journal of Political Science, 2007)
This article gives an account of experimental research conducted in France with focus groups on delinquency. It is based on theoretical work which shows how the political is partly a mode of expression as well as a way of addressing conflict.